2020
DOI: 10.1590/0034-7167-2018-0952
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions and depression in hospital emergency service nurses

Abstract: Objective: to analyze the presence, intensity and factors related to working conditions for depressive symptoms in hospital emergency nurses in the east of São Paulo. Methods: a descriptive, exploratory, quantitative and qualitative study, which applied psychometric scales and interview script. Results: nurses (95.24%) had depressive symptoms by the assessment scales by the observer, most with mild and moderate intensity. Inadequate working conditions led to suffering. Factors that trigger depressive symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(14 reference statements)
0
7
0
1
Order By: Relevance
“…On the other hand, the nursing work environment has been studied using terms such as ‘practice environment’ and ‘working conditions’ and is widely known to affect not only the nurses themselves but also the quality of care (Page, 2004). Previous studies have indicated that the practice environment can affect nurses' mental and physical health (Silva & Marcolan, 2020), job satisfaction (Ogata et al, 2018; Suliman & Aljezawi, 2018), burnout (Hunsaker et al, 2015; Ogata et al, 2018), quality of life and well‐being (Misiak et al, 2020) and work engagement (Al‐Hamdan & Bani Issa, 2021). These effects are then followed by organizational ones such as nurse turnover (Alenazy et al, 2021) and nursing care quality (Aiken et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the nursing work environment has been studied using terms such as ‘practice environment’ and ‘working conditions’ and is widely known to affect not only the nurses themselves but also the quality of care (Page, 2004). Previous studies have indicated that the practice environment can affect nurses' mental and physical health (Silva & Marcolan, 2020), job satisfaction (Ogata et al, 2018; Suliman & Aljezawi, 2018), burnout (Hunsaker et al, 2015; Ogata et al, 2018), quality of life and well‐being (Misiak et al, 2020) and work engagement (Al‐Hamdan & Bani Issa, 2021). These effects are then followed by organizational ones such as nurse turnover (Alenazy et al, 2021) and nursing care quality (Aiken et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…34 Besides, the study by Silva and Marcolan reported that the prevalence of depressive symptoms among emergency nurses in Brazil is 95.24%. 35 Emergency physicians and nurses who had severe depressive symptoms were more likely to be drinking alcohol to regulate these emotional states. 36 Our results are also similar to those reported in a study by Ngasa et al that found that the presence of a chronic disease was independently associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Sørensen et al among 1943 Danish physicians noted that the emergency department had the highest proportion of risky alcohol use 34. Besides, the study by Silva and Marcolan reported that the prevalence of depressive symptoms among emergency nurses in Brazil is 95.24% 35. Emergency physicians and nurses who had severe depressive symptoms were more likely to be drinking alcohol to regulate these emotional states 36.…”
Section: Discussionmentioning
confidence: 99%
“…Their work involves several challenges, including potential ethical dilemmas, working with human suffering, long hours, low pay, lack of time and appropriate space to rest, burden, lack of resources, and low appreciation by other team members. These factors have previously been recognized to cause worsening in the nurses’ mental health 24 , 25 , 27 , and their effects may be exacerbated by the pandemic.…”
Section: Discussionmentioning
confidence: 99%